Low Temperature Stress Tolerance: An Insight Into the Omics Approaches for Legume Crops - Bhat, Kaisar Ahmad; Mahajan, Reetika; Pakhtoon, Mohammad Maqbool; Urwat, Uneeb; Bashir, Zaffar; Shah, Ali Asghar; Agrawal, Ankit; Bhat, Basharat; Sofi, Parvaze A.; Masi, Antonio; Zargar, Sajad Majeed (Frontiers in Plant Science, 2022)
The change in climatic conditions is the major cause for decline in crop production worldwide. Decreasing crop productivity will further lead to increase in global hunger rate. Climate change results in environmental stress which has negative impact on plant like deficiencies in growth, crop yield, permanent damage or death if the plant remains in the stress conditions for prolonged period. Cold stress is one of the main abiotic stresses which have already affected the global crop production. Cold stress adversely affects the plants leading to necrosis, chlorosis, and growth retardation. Various physiological, biochemical and molecular responses under cold stress have revealed that the cold resistance is more complex than perceived which involves multiple pathways. Like other crops, legumes are also affected by cold stress and therefore, an effective technique to mitigate cold-mediated damage is critical for long-term legume production. Earlier, crop improvement for any stress was challenging for scientific community as conventional breeding approaches like inter-specific or inter-generic hybridization had limited success in crop improvement. The availability of genome sequence, transcriptome and proteome data provides in-depth sight into different complex mechanisms under cold stress. Identification of QTLs, genes and proteins responsible for cold stress tolerance will help in improving or developing stress tolerant legume crop. Cold stress can alter gene expression which further leads to increases in stress protecting metabolites to cope up the plant against the temperature fluctuations. Moreover, genetic engineering can help in development of new cold stress tolerant varieties of legume crop. This paper provides a general insight into the ‘omics’ approaches for cold stress in legume crops.